Analysis of the Correspondence Between the Type of Road Damage and the Budget Costs Incurred in Handling on Provincial Roads in the Madura Region - Adi Kurniawan; Andi Patriadi; Sajiyo Sajiyo (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze the suitability between the type of road damage and the budget costs incurred on provincial roads in the Madura region. The research method used road condition survey and questionnaire distribution to contractors, consultants, budget users, and local communities. Data analysis was done descriptively qualitatively, including the type, volume, and location of road damage. The results showed that the three most common types of road damage were cracks, potholes and raveling. The total area of damage identified was 261.95 m², with a repair cost of Rp 57,586,900. This research emphasizes the importance of detailed road defect analysis and appropriate budget allocation to improve repair efficiency and support the region's economic activity. The findings conclude that detailed road defect analysis and budget efficiency can improve road quality and support mobility and economy in the Madura region. The results provide a basis for local governments to plan road infrastructure improvements more effectively and efficiently.